PENINGKATAN KEMAMPUAN MENULIS CERPEN MELALUI PENERAPAN METODE PARTISIPATORI SISWA KELAS VII SMPN 1 PALLANGGA KABUPATEN GOWA. - ANDI PAIDA (JURNAL KONFIKS, 2014)
AbstractThis research was a classroom action research. The research aimed to improve learning outcomes in subjects Indonesian students of class VII SMPN1 Pallangga Gowa through Participatory methods of aspects of the ability to write short stories. Subjects of this study were students of class VII in the first semester of the school year the number of students 2013/2014 41 people. This study was conducted in two cycles, each cycle of meetings held 4 times. Data collection performed by using the achievement test, and the observation sheet. Learning outcomes data were analyzed by using quantitative analysis, while data on observations and student responses analyzed using qualitative analysis. The results showed that the average score of student learning outcomes in the first cycle of 76.95 with a standard deviation from an ideal score of 100, while the second cycle obtained an average score of 77.80 from the ideal score 100 An increase in the thoroughness of the student learning outcomes 37 students (90.24%) which is in the category completed the first cycle to 40 students (97.56%) in the second cycle is already above the 85% completeness limit of classical learning dengaan score of at least 65 per student. Thus, the hypothesis is accepted. Keywords: Short Story Writing Ability Students, Participatory Methods.  AbstrakPenelitian ini adalah penelitian tindakan kelas (Classroom Action Research) yang bertujuan untuk meningkatkan hasil belajar pada mata pelajaran bahasa Indonesia siswa kelas  VII SMPN 1 Pallangga Kabupaten Gowa melalui metode Partisipatori terhadap aspek kemampuan menulis cerpen. Subjek dari penelitian ini adalah siswa kelas VII pada semester ganjil tahun ajaran 2013/2014 dengan jumlah siswa 41 orang. Penelitian  ini dilaksanakan dalam dua siklus, masing-masing siklus dilaksanakan sebanyak 4 kali pertemuan. Pengambilan data dilakukan dengan menggunakan tes hasil belajar, dan lembar observasi. Data hasil belajar yang terkumpul dianalisis dengan menggunakan analisis kuantitatif, sedangkan data hasil observasi dan respon siswa dianalisis dengan menggunakan analisis kualitatif. Hasil penelitian menunjukkan bahwa skor rata-rata hasil belajar siswa pada siklus I sebesar 76,95 dengan standar deviasi  dari skor ideal 100 sedangkan pada siklus II diperoleh skor rata-rata sebesar 77,80  dari skor ideal 100.  Terjadi peningkatan ketuntasan hasil belajar siswa dari 37 siswa (90,24%) yang berada pada kategori tuntas pada siklus I menjadi 40 siswa (97,56%) pada siklus II  sudah berada di atas 85% batas ketuntasan belajar klasikal dengaan skor minimal 65 per siswa. Dengan demikian, hipotesis diterima.Kata Kunci : Menulis Cerpen, Siswa, Metode Partisipatori.